A gene-rich fraction analysis of the Passiflora edulis genome reveals highly conserved microsyntenic regions with two related Malpighiales species - Munhoz, Carla Freitas; Costa, Zirlane Portugal; Cauz-Santos, Luiz Augusto; Egoavil Reategui, Alina Carmen; Rodde, Nathalie; Cauet, Stephane; Dornelas, Marcelo Carnier; Leroy, Philippe; Varani, Alessandro de Mello [UNESP]; Berges, Helene; Carneiro Vieira, Maria Lucia (Nature Publishing Group, 2018)
Passiflora edulis is the most widely cultivated species of passionflowers, cropped mainly for industrialized juice production and fresh fruit consumption. Despite its commercial importance, little is known about the genome structure of P. edulis. To fill in this gap in our knowledge, a genomic library was built, and now completely sequenced over 100 large-inserts. Sequencing data were assembled from long sequence reads, and structural sequence annotation resulted in the prediction of about 1,900 genes, providing data for subsequent functional analysis. The richness of repetitive elements was also evaluated. Microsyntenic regions of P. edulis common to Populus trichocarpa and Manihot esculenta, two related Malpighiales species with available fully sequenced genomes were examined. Overall, gene order was well conserved, with some disruptions of collinearity identified as rearrangements, such as inversion and translocation events. The microsynteny level observed between the P. edulis sequences and the compared genomes is surprising, given the long divergence time that separates them from the common ancestor. P. edulis gene-rich segments are more compact than those of the other two species, even though its genome is much larger. This study provides a first accurate gene set for P. edulis, opening the way for new studies on the evolutionary issues in Malpighiales genomes.